The Association Between Sports Nutrition and Hard Dental Tissue Disorders in Athletes: A Systematic Review - Biskup, Alicja; Wnęk, Agata; Smagowska, Julia; Kala-Kaziszyn, Ewa; Gniewkiewicz, Aleksandra; Hucała, Zuzanna; Jankowska, Natasza (Quality in Sport, 2026)
*]:pointer-events-auto R6Vx5W_threadScrollVars scroll-mb-[calc(var(–scroll-root-safe-area-inset-bottom,0px)+var(–thread-response-height))] scroll-mt-[calc(var(–header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:97a9aaea-383b-4b0e-a55e-f2e76c976030-0" data-turn-id-container="request-WEB:97a9aaea-383b-4b0e-a55e-f2e76c976030-0" data-testid="conversation-turn-2" data-scroll-anchor="false" data-turn="assistant"> <div class="text-base my-auto mx-auto pb-10 [–thread-content-margin:var(–thread-content-margin-xs,calc(var(–spacing)*4))] @w-sm/main:[–thread-content-margin:var(–thread-content-margin-sm,calc(var(–spacing)*6))] @w-lg/main:[–thread-content-margin:var(–thread-content-margin-lg,calc(var(–spacing)*16))] px-(–thread-content-margin)"> <div class="[–thread-content-max-width:40rem] @w-lg/main:[–thread-content-max-width:48rem] mx-auto max-w-(–thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn" data-conversation-screenshot-content=""> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="723d075d-1b44-4308-bad9-65305394c4a6" data-message-model-slug="gpt-5-5" data-turn-start-message="true"> Sports nutrition may influence oral health, particularly through frequent consumption of acidic and sugar-containing products such as isotonic drinks, energy drinks, and carbohydrate supplements. This systematic review evaluated the relationship between sports nutrition and dental hard tissue disorders, mainly dental caries and enamel erosion, in amateur and professional athletes. The reviewed studies suggest that athletes may be at increased risk of caries and enamel erosion due to the cariogenic and erosive potential of sports products. However, the evidence remains inconsistent, as oral health outcomes are also affected by factors such as salivary flow, hydration, fluoride exposure, oral hygiene, and remineralization capacity. Sports nutrition should therefore be regarded as a modifying rather than a direct causative factor in oral diseases. Preventive education and interdisciplinary cooperation between dentists, physicians, and dietitians are important for reducing oral health risks in athletes. Further longitudinal and interventional studies are needed to clarify these relationships.